2020
DOI: 10.21203/rs.3.rs-19596/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different tamponade effects of intraocular silicone oil and sterilized air after single pars plana vitrectomy for rhegmatogenous retinal detachment

Abstract: Purpose: To investigate different fundus vasculature and structure changes after single pars plana vitrectomy (PPV) following silicone oil (SO) or sterilized air in macular-off rhegmatogenous retinal detachment (RRD) patients. Method: 39 eyes (39 patients) with macular-off RRD underwent standard three-port 23-gauge PPV and intraocular SO or gas tamponade. Optical Coherence Tomography (OCT) and angiography were used to evaluate fundus structure and vasculature including retinal layers thicknesses and vessel den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…An interesting study by Zhou et al, involving 39 eyes concluded that the change in retinal thickness following silicone oil tamponade was layer specific, further reporting that the inner nuclear layer and the nerve fiber layer displayed significant decrease in their thickness, whereas the outer nuclear layer, outer plexiform layer and retinal pigment epithelium depicted a significant increase in their thickness. 9 The uniqueness of this study lies in the fact that each layer of the retina behaves differently to the effects exerted by silicone oil tamponade.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting study by Zhou et al, involving 39 eyes concluded that the change in retinal thickness following silicone oil tamponade was layer specific, further reporting that the inner nuclear layer and the nerve fiber layer displayed significant decrease in their thickness, whereas the outer nuclear layer, outer plexiform layer and retinal pigment epithelium depicted a significant increase in their thickness. 9 The uniqueness of this study lies in the fact that each layer of the retina behaves differently to the effects exerted by silicone oil tamponade.…”
Section: Resultsmentioning
confidence: 99%